Martem Accendere Cantu: The meaning of music on the battlefield - Klavan, SA (Brill, 2019)
This paper examines in detail an under-appreciated passage from Philodemus of Gadara’s On Music in order to elucidate several important controversies in Hellenistic musical philosophy. The Stoic Diogenes of Babylon claimed that the emotional impact of trumpet tunes can inspire soldiers to fight. But the Epicurean Philodemus believed that the meaningful words (λόγοι) which stimulate our actions are utterly distinct from meaningless musical sound (µουσική). Philodemus therefore framed an alternative theory in which trumpet calls on the battlefield function not as music but as a kind of makeshift language, using conventional signifiers to communicate instructions. I show how both philosophers’ views arise logically out of doctrines from their respective schools. I then argue that the trumpet’s dual status as both performance instrument and communications device makes it a natural philosophical flashpoint: it raises central questions about what music is, how it affects listeners, and whether it can convey meaning.